Role of the ISKpn element in mediating mgrB gene mutations in ST11 hypervirulent colistin-resistant Klebsiella pneumoniae - Zhu, Lanlan; Li, Ping; Zhang, Guangyi; He, Zhiyong; Tao, Xingyu; Ji, Yicheng; Yang, Wenjing; Zhu, Xiaofang; Luo, Wanying; Liao, Wenjian; Chen, Chuanhui; Liu, Yang; et al. (Frontiers in Microbiology, 2023)
Colistin has emerged as a last-resort therapeutic against antibiotic-resistant bacterial infections, particularly those attributed to carbapenem-resistant Enterobacteriaceae (CRE) like CRKP. Yet, alarmingly, approximately 45% of multidrug-resistant Klebsiella pneumoniae strains now manifest resistance to colistin. Through our study, we discerned that the synergy between carbapenemase and IS elements amplifies resistance in Klebsiella pneumoniae, thereby narrowing the existing therapeutic avenues.